Computational Thinking (CT) Unplugged dalam Pembelajaran Seni Tari di Sekolah Dasar - Rosarina Giyartini; Dwi Alia; Muhammad Rijal Wahid Muharram (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2023)
This research is based on empirical facts, that until now dance arts learning in elementary schools (SD) still uses educational patterns in dance workshops. The orientation is that the student memorizes a certain dance so that the learning method of the student imitates the movement exemplified by the teacher without being given space to creatively process the body based on imagination and all its creative potential. This has an impact on the cover of various intelligences possessed by students. To hack this research seeks to give birth to the concept of dance art learning in elementary school by applying unplugged computational thinking (ct). The goal is that the learning of dance in elementary school is not just to pursue the memorization of motion, but students can creatively realize their creative ideas in the form of dance in accordance with the level of development. To achieve this, the research method used is descriptive analysis. The results of this research in the form of dance learning concepts in elementary schools that apply computational thinking unplugged and ready to be applied